(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Video steganography is the art of information hiding mechanism using multimedia. The purpose of the multimedia is getting enlarged day by day. Face recognition systems are also very useful in many applications such as monitoring system, biometrics and security. Principal Component Analysis (PCA) has also been used in some important applications, especially in pattern detection such as face detection and recognition. In real-time applications, the response time must be as small as possible and security must be at a higher level. Steganography and cryptography in computer forensics.